The impact of a player scoring system on cognitive, affective and behavioural outcomes of players in a talent identification and development environment - Ashford, M.; Burke, K.; Barrell, D.; Abraham, A.; Poolton, J. (The Journal of Sport and Exercise Science, 2022)
Rule changes in sport are relatively common. They are typically instigated in response to concerns around player safety (e.g., tackle height in rugby), game flow and entertainment (e.g., shot clock in basketball), or to facilitate talent development processes (e.g., reduced team size in junior football). The purpose of this study was to monitor the impact of a modified scoring system created by the Rugby Football Union as a vehicle to shape desired cognitive, affective and behavioural outcomes in a talent development setting. We asked players to describe their learning experiences of the scoring system preceding competition, their approach to the scoring system, and its impact on their decision-making. Key performance indicators (Total Carries, Total Points & Points Per Carry) were collected to monitor player effectiveness across three competitive games. Semi-structured interviews and psychometric scales were used to gain insight into the players learning experiences, feelings, decision making and declarative knowledge. Our findings indicated that players learning experiences affected how well-prepared players felt to perform (affective); the acquisition and use of task-specific declarative knowledge (cognitive); and the effectiveness of players carrying the ball into contact (behavioural).